2010
DOI: 10.2176/nmc.50.645
|View full text |Cite
|
Sign up to set email alerts
|

Two-Level Anterior Lumbar Interbody Fusion With Percutaneous Pedicle Screw Fixation: A Minimum 3-Year Follow-up Study

Abstract: The clinical and radiological outcomes of two-level anterior lumbar interbody fusion (ALIF) with percutaneous pedicle screw fixation (PSF) were evaluated in 24 consecutive patients who underwent twolevel ALIF with percutaneous PSF for segmental instability and were followed up for more than 3 years. Clinical outcomes were assessed using a visual analogue scale (VAS) score and the Oswestry Disability Index (ODI). Sagittal alignment, bone union, and adjacent segment degeneration (ASD) were assessed using radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Indeed, such efforts have boosted fusion rates. 2,13,14,16,32 Stand-alone cages with intrinsic plates and screws have also been developed to address needed restoration of the anterior tension band. 15 Cage stability in flexion, extension, and lateral bending now compares favorably with pedicle screw fixation and is superior with respect to rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such efforts have boosted fusion rates. 2,13,14,16,32 Stand-alone cages with intrinsic plates and screws have also been developed to address needed restoration of the anterior tension band. 15 Cage stability in flexion, extension, and lateral bending now compares favorably with pedicle screw fixation and is superior with respect to rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Meandros Med Dent J In the literatüre, many different surgical procedures have been described in terms of surgical treatment of spondylolisthesis (10)(11)(12)(13). The main purpose of these surgical procedures is to eliminate pain caused by instability, to remove compression causing neurological deficits in patients, to restorate normal spinal alignment by correcting the sagittal imbalance secondary to spondylolisthesis and to prevent the progression of spondylolisthesis by advancing the areas of fusion in medium and long term.The PLF is presented as a gold standard method in spondilolistezis by some authors because pedicle screw fixation systems have advantages such as theoretically the reduction of spondylolisthesis and the correction of deformity and also have been reported to increase fusion rates of rigid fixation (7,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment is applied in patients with neurological deficit who do not benefit from physical therapy and conservative treatment (9). In the literature, many surgical techniques such as anterior interbody fusion, posterolateral fusion (PLF),posterior lumbar interbody fusion, circumflexial fusion, transforaminal interbody fusion and axial lumbar interbody fusion have been described (10)(11)(12)(13).Although many different techniques have been described for the surgical treatment of spondylolisthesis, posterolateral lumbar fusion is regarded as the gold standard (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Loguidice et al 55 and Dennis et al 56 retrospectively compared cadaveric allografts and autografts and found no statistically significant differences in fusion rates. One study using freeze-dried allogenic corticocancellous bone in polyetheretherketone cages in stand-alone ALIF procedures reported unfavorable fusion rates of 70.6% 57 , whereas other studies that have evaluated the use of allografts in cages in conjunction with percutaneous pedicle fixation have reported fusion rates as high as 87.5%-100% [58][59][60][61][62] . Moreover, donor site complications are avoided with the use of allografts.…”
Section: Allograftsmentioning
confidence: 99%